WORKSHOP IMPLEMENTASI KURIKULUM MERDEKA BELAJAR PADA GURU SEKOLAH DASAR GUGUS I KECAMATAN SUMBER HARTA - Valen, Andri; Frima, Aren; Andita, Cahyo Dwi; Maharani, Tidi (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2023)
PKM was motivated by the results of observations that elementary school teachers in Sumber Harta sub-district had not received socialization and training on designing learning tools and independent learning curriculum evaluation tools so that socialization and training were needed to prepare learning tools and independent learning curriculum evaluation tools. The main goal of PKM is to make teachers more professional and improve teacher pedagogic competence with regard to the ability to manage, design learning tools, and carry out learning and evaluate learning outcomes. The method applied is through a scheme of providing materials, training, and mentoring. The PKM was held at Sumber Harta 1 Public Elementary School, which was attended by 23 participants from the teachers of the Gugus I Elementary School, Sumber Harta District, Musi Rawas Regency. The results of the PKM were the implementation of socialization activities and training in the preparation of independent learning curriculum learning tools. Elementary School teachers at Cluster 1 Sumber Harta District have knowledge and skills regarding the Implementation of the Free Learning Curriculum. Teachers can also develop skills in making Learning Toolkits, Modules, LKPD, and Independent Curriculum Evaluation Instruments properly and professionally and increase capacity/expertise up to recognized competencies.